2015
DOI: 10.1128/jvi.03468-14
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Decay-Accelerating Factor on Intestinal Epithelium of Transgenic Mice Does Not Facilitate Infection by the Enteral Route

Abstract: In vitro, infection of polarized human intestinal epithelial cells by coxsackievirus B3 (CVB3) depends on virus interaction with decay-accelerating factor (DAF), a receptor expressed on the apical cell surface. Although mice are highly susceptible to CVB3 infection when virus is delivered by intraperitoneal injection, infection by the enteral route is very inefficient. Murine DAF, unlike human DAF, does not bind virus, and we hypothesized that the absence of an accessible receptor on the intestinal surface is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
(36 reference statements)
2
10
0
Order By: Relevance
“…These findings illuminate clear differences between the natural human host, and the murine model of infection. Expression of the human form of DAF on the intestinal epithelium in transgenic mice failed to facilitate infection by the enteral route (Pan, Zhang et al, 2015), suggesting that other obstacles such as the type I interferon response (Ohka, Igarashi et al, 2007) and interactions with the intestinal flora (Kuss, Etheredge et al, 2008) may limit CVB infection in the murine model.…”
Section: Introductionmentioning
confidence: 99%
“…These findings illuminate clear differences between the natural human host, and the murine model of infection. Expression of the human form of DAF on the intestinal epithelium in transgenic mice failed to facilitate infection by the enteral route (Pan, Zhang et al, 2015), suggesting that other obstacles such as the type I interferon response (Ohka, Igarashi et al, 2007) and interactions with the intestinal flora (Kuss, Etheredge et al, 2008) may limit CVB infection in the murine model.…”
Section: Introductionmentioning
confidence: 99%
“…Although murine models have been developed for the study of enterovirusinduced disease (1)(2)(3)(4), many of these models require intraperitoneal (i.p.) infection, thereby bypassing the GI tract, or require ablation of the host innate immune system (5,6). Coupled with species differences between humans and mice, there remains a need to develop human-based platforms to model enterovirus infections of the GI tract.…”
mentioning
confidence: 99%
“…DAF, a co-receptor of CAR, is expressed on CD4 + T cells and facilitates CVB3 internalization by increasing the binding efficiency of CVB3 on the DAF-CAR complex. Although Patel et al considered that the interaction between CVB3 and DAF alone was insufficient for CVB3 infection (Patel et al, 2009), Pan et al indicated that CVB3 infection of human intestinal epithelial cells without CAR expression was dependent on DAF (Pan et al, 2015). Furthermore, Martino et al showed that anti-DAF mAb blocked coxsackie virus infection of susceptible HeLa cells by reducing viral adhesion and internalization (Martino et al, 1998).…”
Section: Discussionmentioning
confidence: 99%